2010
DOI: 10.1152/ajpgi.00344.2009
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β downregulates PTEN via activation of NF-κB in pancreatic cancer cells

Abstract: TGF-beta utilizes receptor-activated SMAD signaling to mediate growth suppression; however, non-SMAD signaling that modulates the TGF-beta response in epithelial cells become apparent when the SMAD signaling is abrogated, a common occurrence in pancreatic cancers. Here, we examined whether TGF-beta utilized NF-kappaB to downregulate PTEN, a gene that is rarely mutated in pancreatic cancers. SMAD4-null BxPc3 and CAPAN-1 pancreatic cancer cells were treated with TGF-beta (10 ng/ml) and lysed, and cellular protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 28 publications
0
29
0
Order By: Relevance
“…Furthermore, the fact that we did not observe NFB activation by TGF treatment of SMAD4-positive Panc1 cells is consistent with a recent report in the SMAD4-negative pancreatic cancer cell line BxPC3. Here, TGF-dependent activation of NFB is abolished by the re-expression of SMAD4 (Chow et al, 2010). However, the SMAD4-dependent mechanism blocking TGF-dependent NFB activation remains unclear at the molecular level.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the fact that we did not observe NFB activation by TGF treatment of SMAD4-positive Panc1 cells is consistent with a recent report in the SMAD4-negative pancreatic cancer cell line BxPC3. Here, TGF-dependent activation of NFB is abolished by the re-expression of SMAD4 (Chow et al, 2010). However, the SMAD4-dependent mechanism blocking TGF-dependent NFB activation remains unclear at the molecular level.…”
Section: Discussionmentioning
confidence: 99%
“…78,79 (v) It has been clearly demonstrated that the action of TGF-b is induced through the activation of NF-kB. 25,26,75,76,80,81 At the same time, it has been reported that NF-kB activation induces TGF-b production. [82][83][84] Thus, there is a potential positive feedback mechanism between TGF-b production and NF-kB activation that enhances the fibrotic process.…”
Section: Discussionmentioning
confidence: 99%
“…It is established that activation of NF-B results in downregulation of PTEN expression (38)(39)(40). The downregulation of PTEN leads to increased recruitment of macrophages and elevated levels of proinflammatory cytokines and chemokines in inflamed lungs, which, in turn, is thought to induce increased neutrophil recruitment to the lungs.…”
Section: Discussionmentioning
confidence: 99%